TEACHING DESCRIPTVE TEXT WRITING BY USING ANIMATED VIDEO - Dwi Yuza, Maqdisa Id ha; Supardi, Iwan; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research was to find out the effectiveness of animated video in teaching writing descriptive text to the eighth grade students of SMPN 14 Pontianak in academic year 2018/2019. The population of this research was the eighth grade students of SMPN 14 Pontianak in academic year 2018/2019. The researcher took the sample by using cluster random sampling technique. The sample of this research was the students of class VIII B which consisted of 24 students. The data were collected through measurement technique and written test. The data showed that the effect size of the treatment was 0.85, and it was categorized as moderate effect. The findings of the research obviously showed that the used of animated video was significantly effective to teach writing descriptive text to the eighth grade students of SMPN 14 Pontianak in academic year 2018/2019. Keywords: Writing, Descriptive Text, Animated VideoÂ